Effect of shrinkage on cracking and structural behaviour of reinforced glulam members. (11th April 2022) - Danzer, Martin; Dietsch, Philipp; Winter, Stefan
Highlights: Load-carrying capacities of reinforced glulam beams before and after shrinkage Numerical model to determine critical changes in wood moisture content Quantification of critical changes in wood moisture content for practical applications Practical recommendations to reduce the restraining effect of reinforcing elements Abstract: This paper deals with the question whether and to what extent reinforcing elements have a negative impact on the structural behavior of glulam members due to their potential of restraining the free shrinkage behavior of wood. For this purpose, experimental and numerical investigations were performed on three groups of reinforced glulam members (homogeneous arrangements, holes, notches) to quantify the restraining effect of the reinforcing elements. In experimental investigations the test specimens were first exposed to a slow drying process and analyzed regarding the parameters distribution of wood moisture, crack formation and shrinkage deformations. After climate storage destructive tests were realized on all test specimens with holes and notches to quantify the restraining effect by determining the decrease in load-carrying capacity. In case of beams with reinforced holes, the load-carrying capacity decreased to around 65 % − 79 % and to around 69 % − 83 % in case of beams with notches, the extent of the reduction depending on the type and arrangement of the reinforcement. The experimental investigations were extended by numerical investigations based on three-dimensional simulation models, considering the lamella structure of glulam as well as the cylindrical orthotropy of the wood structure. Critical differential moisture contents for an onset of cracking were determined by implementing a steady-state change of moisture content, followed by a probability-based evaluation of the stressed volume in tension perpendicular to the grain. Parameter studies on the three groups of reinforced glulam members showed, that an onset of cracking is influenced in particular by the quantity of reinforcing elements, their inclination to grain direction, the member height and the axial withdrawal stiffness of the reinforcement. All four influencing factors have a negative effect on the formation of cracks with increasing magnitude.